Application of Kβ/Kα in selecting calibration standards for X‐ray fluorescence analysis. (24th June 2019) - She, Xiaomeng; Zhu, Zhixiu; Gao, Jie; Qian, Rong; Sheng, Cheng; Shen, Ruxiang; Zhuo, Shangjun
Abstract : A method for improving the accuracy in X‐ray fluorescence spectroscopy analysis with pressed pellets was established through matching the calibration standards by the Kβ/Kα ratios. The Kβ/Kα ratios of four major elements (Al, Si, Ca, and Fe) were measured in 14 certified reference materials (CRMs) for geochemistry. The deviation of the biggest Kβ/Kα values relative to the smallest ones for the same element was from 1.52% (Si) to 20.98% (Al) when pressed pellets were used. The relative deviation of Kβ/Kα values for Ca was as high as 3.56% even for two soil CRMs (GBW07404 and GBW07408). X‐ray diffraction analysis confirmed that the Ca elements in the two CRMs were in distinct phases, thereby leading to the different Kβ/Kα values. The Fundamental Parameter Method (FPM) results of two calibration strategies were compared. When one of the 14 CRMs was selected as unknown sample whereas the other 13 CRMs were used for calibration to determine Al2 O3, SiO2, CaO, and Fe2 O3, the relative errors were 10.80%, 8.77%, 8.33%, and 10.91%, respectively. Another strategy, where only one CRM was used for calibration of samples with large errors, was adopted by matching Kβ/Kα values. The results of calibrating using CRM with similar Kβ/Kα values were more accurate than those with different Kβ/Kα values.